International law - Klabbers, Jan (Cambridge [UK] ; New York : Cambridge University Press, 2018)
"Written by one of the world's leading international lawyers, this is the new and updated edition of Jan Klabber's landmark textbook. International law can be defined as 'the rules governing the legal relationship between nations and states', but in reality it is much more complex, with political, diplomatic and socio-economic factors shaping the law and its application. This refreshingly clear, concise textbook encourages students to view international law as a dynamic system of organizing the world. Bringing international law back to its first principles, the book is organised around four questions: where does it come from? To whom does it apply? How does it resolve conflict? And what does it say? Building on these questions with both academic rigour and clarity of expression, Professor Klabbers breathes life and energy into the subject. Footnotes point students to the wider academic debate while chapter introductions and final remarks reinforce learning. The second edition has been updated throughout, with particular attention to recent judicial decisions, and features new sections on sovereign debt relief, the prompt release of vessels, and the Antarctic"--
Machine generated contents note: Part I. The Structure of International Law: 1. The setting of international law; 2. The making of international law; 3. The law of treaties; 4. The subjects of international law; 5. Jurisdiction, powers and immunities; 6. The individual in international law, including human rights; 7. The law of responsibility; 8. International courts and tribunals; 9. Sanctions, countermeasures and collective security; Part II. The Substance of International Law: 10. Use of force; 11. The law of armed conflict; 12. International criminal law; 13. The seas, the air and outer space; 14. Protecting the environment; 15. The global economy; Part III. The Surroundings of International Law: 16. Domestic courts and their relationship with international law; 17. The politics and ethics of international law and global governance; 18. By way of conclusion; Bibliography; Index.
Includes bibliographical references (pages 353-357) and index.
Keywords: International law